Cancer Therapy–Related Hypertension: A Scientific Statement From the American Heart Association. Issue 3 (9th January 2023) - Cohen, Jordana B.; Brown, Nancy J.; Brown, Sherry-Ann; Dent, Susan; van Dorst, Daan C.H.; Herrmann, Sandra M.; Lang, Ninian N.; Oudit, Gavin Y.; Touyz, Rhian M.
Abstract : Contemporary anticancer drugs have significantly improved cancer survival at the expense of cardiovascular toxicities, including heart disease, thromboembolic disease, and hypertension. One of the most common side effects of these drugs is hypertension, especially in patients treated with vascular endothelial growth factor inhibitors, as well as tyrosine kinase inhibitors and proteasome inhibitors. Adjunctive therapy, including corticosteroids, calcineurin inhibitors, and nonsteroidal anti-inflammatories, as well as anti-androgen hormone therapy for prostate cancer, may further increase blood pressure in these patients. Cancer therapy–induced hypertension is often dose limiting, increases cardiovascular mortality in cancer survivors, and is usually reversible after interruption or discontinuation of treatment. The exact molecular mechanisms underlying hypertension are unclear, but recent discoveries indicate an important role for reduced nitric oxide generation, oxidative stress, endothelin-1, prostaglandins, endothelial dysfunction, increased sympathetic outflow, and microvascular rarefaction. In addition, genetic polymorphisms in vascular endothelial growth factor receptors are implicated in vascular endothelial growth factor inhibitor–induced hypertension. Diagnosis, management, and follow-up of cancer therapy–induced hypertension follow national hypertension guidelines because evidence-based clinical trials specifically addressing patients who develop hypertension as a result of cancer therapy are currently lacking. Rigorous baseline assessment of patients before therapy is started requires particular emphasis on assessing and treating cardiovascular risk factors. Hypertension management follows guidelines for the general population, although special attention should be given to rebound hypotension after termination of cancer therapy. Management of these complex patients requires collaborative care involving oncologists, cardiologists, hypertension specialists, primary care professionals, and pharmacists to ensure the optimal therapeutic effect from cancer treatment while minimizing competing cardiovascular toxicities.